2016
DOI: 10.1007/s40615-016-0322-0
|View full text |Cite
|
Sign up to set email alerts
|

Research Professionals’ Perspectives, Barriers, and Recommendations Regarding Minority Participation in Clinical Trials

Abstract: Despite a few subtle racial differences in research professionals' perspectives, a majority expressed no hesitation in enrolling minorities. Patients' race and primary language appeared to influence enrollment. A language barrier appeared to be the strongest barrier for research professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Until existing enrollment biases are eliminated, novel study designs, such as the present study, will be necessary to construct clinical databases more representative of US demographics. Counter to prevailing beliefs and a report suggesting that nonwhite race and patient-physician language discordance serve as impediments to clinical trial enrollment, 26 we demonstrate that, with appropriate site se-lection and concerted effort, women and minorities can be enrolled in a large, national, multicenter PCI outcomes study at a rate comparable with conventional studies. By completing enrollment 6 months ahead of schedule, the PD study enrolled patients faster than PE Plus.…”
Section: Discussionmentioning
confidence: 99%
“…Until existing enrollment biases are eliminated, novel study designs, such as the present study, will be necessary to construct clinical databases more representative of US demographics. Counter to prevailing beliefs and a report suggesting that nonwhite race and patient-physician language discordance serve as impediments to clinical trial enrollment, 26 we demonstrate that, with appropriate site se-lection and concerted effort, women and minorities can be enrolled in a large, national, multicenter PCI outcomes study at a rate comparable with conventional studies. By completing enrollment 6 months ahead of schedule, the PD study enrolled patients faster than PE Plus.…”
Section: Discussionmentioning
confidence: 99%
“…19 Another study in 2017 claims language and repeated follow-ups of the patient and record maintenance a barriers to research. 20 With current study findings and previous data available, it is concluded that a widespread adaptation of system-based reforms should be launched to help, educate, guide, counsel and facilitate research students. This will not only encourage them but also make it easily accessible for them.…”
Section: Discussionmentioning
confidence: 64%
“…BSSR approaches can help with the development of materials to support understanding of HIV cure research so that diverse groups can more easily participate in and contribute to HIV cure research. BSSR can help ensure that participants mirror the HIV epidemic when testing HIV cure interventions, so that results are more generalizable, and interventions are safe and effective in all populations .…”
Section: Discussionmentioning
confidence: 99%